Influence of the Shaping on Tribological Properties of PEEK‐Coated U‐Shaped Metal‐Profiles1. Issue 9 (12th April 2013) - Josch, Lena E.; Götz, Volker; Römer, Christian; Konchakova, Natalia; Emrich, Stefan; Wagner, Christine; Müller, Ralf; Kopnarski, Michael; Schlarb, Alois K.
<x xml:space="preserve">Abstract</x> Composite bearings are normally produced with a layer of sintered bronze between the polymer coating and the metallic substrate, but omitting the extra bronze layer would reduce cost and manufacturing complexity. In this work, thermal impact welded metal‐polymer composite specimen without sintered bronze layer are shaped to U‐half shells to test them in a tribological test set up that is similar to the situation in a bearing. Wear rates and friction coefficient are measured for different pressure and velocity combinations. The effects of the shaping and their influence on wear behavior are examined by surface analysis, e.g., with SEM. Beside those shaping effects the heat balance is a very important influencing parameter on friction and wear behavior.